Amplification of Ultrashort Titan-sapphire Laser Pulses Using Chirped-pulse Amplification Technique - Thong, Pham Huy; Tu, Nguyen Xuan; Diep, Nguyen Van; Duong, Pham Van; Minh, Pham Hong; Bich, Vu Thi; Buganov, O. A.; Tikhomirov, S. A.; Cadatal-Raduban, Marilou (Communications in Physics, 2019)
We report on a Chirped Pulse Amplification (CPA)-based Titanium:Sapphire (Ti:Al2O3 or Ti:Sapphire) amplifier that uses a single grating stretcher and compressor configuration. The 8-pass amplifier configuration is able to yield 70 μJ pulse energy at 10 Hz repetition rate, which corresponds to a gain of 7000 times. The amplified pulses are expected to be transform-limited with pulse duration of 85 fs. This amplifier will expand the application of our Ti:Sapphire laser at the Vietnam Academy of Sciences (VAST).